The ER cholesterol sensor SCAP promotes CARTS biogenesis at ER–Golgi membrane contact sites - Wakana, Yuichi (J Cell Biol, 2020)
In response to cholesterol deprivation, SCAP escorts SREBP transcription factors from the endoplasmic reticulum to the Golgi complex for their proteolytic activation, leading to gene expression for cholesterol synthesis and uptake. Here, we show that in cholesterol-fed cells, ER-localized SCAP interacts through Sac1 phosphatidylinositol 4-phosphate (PI4P) phosphatase with a VAP–OSBP complex, which mediates counter-transport of ER cholesterol and Golgi PI4P at ER–Golgi membrane contact sites (MCSs). SCAP knockdown inhibited the turnover of PI4P, perhaps due to a cholesterol transport defect, and altered the subcellular distribution of the VAP–OSBP complex. As in the case of perturbation of lipid transfer complexes at ER–Golgi MCSs, SCAP knockdown inhibited the biogenesis of the trans-Golgi network–derived transport carriers CARTS, which was reversed by expression of wild-type SCAP or a Golgi transport–defective mutant, but not of cholesterol sensing–defective mutants. Altogether, our findings reveal a new role for SCAP under cholesterol-fed conditions in the facilitation of CARTS biogenesis via ER–Golgi MCSs, depending on the ER cholesterol.